Lack of Functional Receptors Is the Only Barrier That Prevents Caprine Arthritis-Encephalitis Virus from Infecting Human Cells - Mselli-Lakhal, Laila (American Society for Microbiology, 2000)
Barriers to replication of viruses in potential host cells may occur at several levels. Lack of suitable and functional receptors on the host cell surface, thereby precluding entry of the virus, is a frequent reason for noninfectivity, as long as no alternative way of entry (e.g., pinocytosis, antibody-dependent adsorption) can be exploited by the virus. Other barriers can intervene at later stages of the virus life cycle, with restrictions on transcription of the viral genome, incorrect translation and posttranslational processing of viral proteins, inefficient viral assembly, and release or efficient early induction of apoptosis in the infected cell. The data we present here demonstrate that replication of caprine arthritis-encephalitis virus (CAEV) is restricted in a variety of human cell lines and primary tissue cultures. This barrier was efficiently overcome by transfection of a novel infectious complete-proviral CAEV construct into the same cells. The successful infection of human cells with a vesicular stomatitis virus (VSV) G-pseudotyped Env-defective CAEV confirmed that viral entry is the major obstacle to CAEV infection of human cells. The fully efficient productive infection obtained with the VSV-G-protein-pseudotyped infectious CAEV strengthened the evidence that lack of viral entry is the only practical barrier to CAEV replication in human cells. The virus thus produced retained its original host cell specificity and acquired no propensity to propagate further in human cultures.